2011
DOI: 10.1159/000319969
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Aquaporins and Sodium Transporter Proteins in the Solitary Kidney in Response to Partial Ureteral Obstruction in Neonatal Rats

Abstract: Unilateral ureteral obstruction (UUO) impairs function of the obstructed kidney, and the contralateral nonobstructed kidney compensates depending on the degree and duration of UUO. This study aimed to determine the hemodynamic and molecular changes in the solitary kidney in response to partial ureteral obstruction (PUO) where any compensation from the contralateral kidney was eliminated so that all observed changes in the kidney tissue occurred in the kidney with PUO. Newborn rats were subjected to unilateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
(50 reference statements)
2
3
0
Order By: Relevance
“…It seems that the protective role of estradiol in renal system was not certain. Previously, it is reported that UUO is accompanied with increasing of serum BUN and Cr levels (10), reduction of GFR about 20-70% (11,12), decreasing of tubular injury and interstitial fibrosis (13), reduction of UNaV and urine osmolality (14), and increasing of fibronectin expression (15). In our study, the serum level of BUN and Cr were increased by UUO possibly by renal fibrosis or GFR reduction.…”
Section: Discussionsupporting
confidence: 64%
“…It seems that the protective role of estradiol in renal system was not certain. Previously, it is reported that UUO is accompanied with increasing of serum BUN and Cr levels (10), reduction of GFR about 20-70% (11,12), decreasing of tubular injury and interstitial fibrosis (13), reduction of UNaV and urine osmolality (14), and increasing of fibronectin expression (15). In our study, the serum level of BUN and Cr were increased by UUO possibly by renal fibrosis or GFR reduction.…”
Section: Discussionsupporting
confidence: 64%
“…A similar phenomenon was observed in both BUO and UUO [8,9]. A study with partial ureteral obstruction also showed a decrease in AQP 1 [10].…”
Section: Pathogenesissupporting
confidence: 73%
“…reported that GFR, urine osmolality, and urinary sodium excretion were reduced in solitary kidney with UUPJO. [20] In rodent models, both partial and complete obstruction resulted in alteration in urinary osmolytes. [21] While acute short-term unilateral obstruction in rats has not changed the permeability to water and reabsorptive capacity of terminal collecting duct, prolonged unilateral obstruction has resulted in increased cyclooxygenase and decreased permeability to water and urinary sodium excretion in obstructed kidney.…”
Section: Discussionmentioning
confidence: 99%